Review on nanostructured photoelectrodes for next generation dye-sensitized solar cells - José Maçaira (2013)
This work reviews the state-of-the-art nanostructured photoelectrodes for use in dye-sensitized solar cells. The influence of the photoelectrode structure in the DSC performance is analyzed. The nanostructured photoelectrodes can be classified into: (1) nanoparticles with high surface areas for efficient dye loading; (2) 1D nanostructures such as nanotubes and nanowires that offer direct electron transport pathways towards the collecting substrate; (3) 3D hierarchically ordered photoelectrodes that combine large pores for efficient electrolyte diffusion, large particles for effective light scattering but also small particles needed to achieve high surface areas; (4) 3D template-based techniques that create highly conductive macroporous scaffolds to produce structures with different length scales for electrolyte diffusion (macro and mesopores) and dye loading (micro and nanopores); and finally (5) hybrid TiO2/ graphene nanostructures able to suppress electron recombination in the semiconductor/electrolyte interface, increasing the electron mobility and extraction and also able to enhance light absorption, ultimately increasing the DSC performance.